Serapan Hara N, P dan K Tanaman Jagung (Zea mays L.) di Dutohe Kabupaten Bone Bolango - Mayang, Hariyanto; ., Nurdin; Jamin, Fitriah S. (Jurnal Agroteknotropika, 2012)
This study aimed to determine the N, P, and K nutrients uptakes of maize crops in Dutohe of Bone Bolango regency. Te research was carried out in Dutohe Village of Kabila Distric of Bone Bolango regency for about 6 months. The experimental design was following randomized block design that consist of 4 treatments (P+K, N+P, N+K) with 3 replications, so there are 12 plot units. Dosages of each treatment were 160 kg Urea, 54 kg TSP, and 90 kg KCl. The result from the experiment showed that minus one test has not significant effect to N and P uptakes, but has significant effect to K uptake.